Structural Design of Ionic Liquids for Optimizing Aromatic Dissolution. Issue 1 (9th November 2018) - Jiang, Haihui Joy; Imberti, Silvia; Simmons, Blake A.; Atkin, Rob; Warr, Gregory G.
Abstract: Certain protic ionic liquids (PILs) are potentially low‐cost, high‐efficiency solvents for the extraction and processing of aromatic compounds. To understand the key design features of PILs that determine solubility selectivity at the atomic level, neutron diffraction was used to compare the bulk structure of two PILs with and without an aromatic solute, guaiacol (2‐methoxyphenol). Guaiacol is a common lignin residue in biomass processing, and a model compound for anisole‐ or phenol‐based food additives and drug precursors. Although the presence of amphiphilic nanostructure is important to facilitate the dissolution of solute nonpolar moieties, the local geometry and competitive interactions between the polar groups of the cation, anion, and solute are found to also strongly influence solvation. Based on these factors, a framework is presented for the design of PIL structure to minimize competition and to enhance driving forces for the dissolution of small aromatic species. Abstract : Non‐stop protic cabaret : To understand the key design features of protic ionic liquids (PILs) that determine solubility selectivity at the atomic level, neutron diffraction is used to compare the bulk structure of two PILs with and without an aromatic solute, guaiacol. The local geometry and competitive interactions between the polar groups of the cation, anion, and solute are found to strongly influence solvation.